Nickelate Superconductivity without Rare‐Earth Magnetism: (La, Sr)NiO2. Issue 45 (18th September 2021) - Osada, Motoki; Wang, Bai Yang; Goodge, Berit H.; Harvey, Shannon P.; Lee, Kyuho; Li, Danfeng; Kourkoutis, Lena F.; Hwang, Harold Y.
Abstract: The occurrence of unconventional superconductivity in cuprates has long motivated the search for manifestations in other layered transition metal oxides. Recently, superconductivity is found in infinite‐layer nickelate (Nd, Sr)NiO2 and (Pr, Sr)NiO2 thin films, formed by topotactic reduction from the perovskite precursor phase. A topic of much current interest is whether rare‐earth moments are essential for superconductivity in this system. In this study, it is found that with significant materials optimization, substantial portions of the La1− x Sr x NiO2 phase diagram can enter the regime of coherent low‐temperature transport ( x  = 0.14 ‐ 0.20), with subsequent superconducting transitions and a maximum onset of ≈9 K at x  = 0.20. Additionally, the unexpected indication of a superconducting ground state in undoped LaNiO2 is observed, which likely reflects the self‐doped nature of the electronic structure. Combining the results of (La/Pr/Nd)1− x Sr x NiO2 reveals a generalized superconducting dome, characterized by systematic shifts in the unit cell volume and in the relative electron‐hole populations across the lanthanides. Abstract : By refining the synthesis of high‐quality thin films, a superconducting dome is observed in La1− x Sr x NiO2 . Perhaps more surprisingly, undoped LaNiO2 also shows a strong indication of superconductivity. A generalized superconducting dome can be obtained by combining the La/Pr/Nd systems, revealing systematic shifts in the unit cell volume and the relative electron–hole population across the lanthanides.